Officers of the Society (Journal of Labor Economics, 2021)
Previous articleNext article FreeOfficers of the SocietyPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMore2021–23 Board of Officers of the SocietyPresident (2021–22): Kevin Lang, Boston UniversityPresident-Elect (2022–23): Thomas Lemieux, University of British ColumbiaVice President (2023–24): Kathryn Shaw, Stanford University2020–22: Claudia Olivetti, Dartmouth College2020–22: Lisa Kahn, Rochester University2021–23: Hilary Hoynes, University of California, Berkeley2021–23: Barbara Petrongolo, University of OxfordKevin Lang, Boston University and the Journal of Labor Economics, ex officioFellows of the Society of Labor EconomistsJohn AbowdKatharine AbrahamDaron AcemogluGeorge AkerlofJoseph AltonjiJoshua AngristOrley AshenfelterDavid AutorAnn BartelGary Becker*Marianne BertrandDan BlackSandra BlackRebecca BlankFrancine BlauRichard BlundellGeorge BorjasJohn BoundCharles BrownKenneth BurdettGlen Cain*David CardKerwin Kofi CharlesPierre-Andre ChiapporiJanet CurrieSteven J. DavisJohn DiNardo*Christian DustmannRon EhrenbergHenry FarberNicole FortinRichard FreemanVictor FuchsRoland G. FryerRobert GibbonsClaudia GoldinReuben GronauRobert HallJohn HaltiwangerDan HamermeshEric HanushekJames HeckmanV. Joseph HotzCaroline M. HoxbyHilary HoynesGeorge Johnson*Chinhui JuhnLawrence KahnLawrence KatzJohn KennanFrancis KramarzAlan Krueger*Robert J. LaLonde*Kevin LangRichard LayardEdward Lazear*Thomas LemieuxShelly LundbergStephen MachinW. Bentley MacLeodThomas MaCurdyAlan ManningAlexandre MasMarjorie McElroyCostas MeghirRobert MichaelJacob Mincer*Robert MoffittEnrico MorettiDale Mortensen*Richard MurnaneKevin MurphyDerek NealSteve NickellWalter Oi*John PencavelChristopher PissaridesRobert PollakCanice PrendergastMelvin Reder*Mark RosenzweigKathryn ShawRob ShimerJames SmithJeffrey SmithGary SolonFrank StaffordChris TaberPetra ToddRobert TopelJohn Van ReenenYoram WeissFinis WelchRobert WillisNew Fellows Elected in 2021Michael KeaneMagne MogstadPaul OyerCecila RouseKjell SalvanesNotes*Deceased. Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 39, Number 3July 2021 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/715496 Views: 544Total views on this site © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.